Ideal homes, 1918-39 : domestic design and suburban modernism - Ryan, Deborah S. (Studies in design and material culture., 2018)
This book explores the aspirations and tastes of new suburban communities in interwar England for domestic architecture and design that was both modern and nostalgic in a period where homeownership became the norm.